Heterozygous STAT1 gain-of-function mutations underlie an unexpectedly broad clinical phenotype. - Toubiana, Julie (2016)
Since their discovery in patients with autosomal dominant (AD) chronic mucocutaneous candidiasis (CMC) in 2011, heterozygous STAT1 gain-of-function (GOF) mutations have increasingly been identified worldwide. The clinical spectrum associated with them needed to be delineated. We enrolled 274 patients from 167 kindreds originating from 40 countries from 5 continents. Demographic data, clinical features, immunological parameters, treatment, and outcome were recorded. The median age of the 274 patients was 22 years (range, 1-71 years); 98% of them had CMC, with a median age at onset of 1 year (range, 0-24 years). Patients often displayed bacterial (74%) infections, mostly because of Staphylococcus aureus (36%), including the respiratory tract and the skin in 47% and 28% of patients, respectively, and viral (38%) infections, mostly because of Herpesviridae (83%) and affecting the skin in 32% of patients. Invasive fungal infections (10%), mostly caused by Candida spp. (29%), and mycobacterial disease (6%) caused by Mycobacterium tuberculosis, environmental mycobacteria, or Bacille Calmette-Guérin vaccines were less common. Many patients had autoimmune manifestations (37%), including hypothyroidism (22%), type 1 diabetes (4%), blood cytopenia (4%), and systemic lupus erythematosus (2%). Invasive infections (25%), cerebral aneurysms (6%), and cancers (6%) were the strongest predictors of poor outcome. CMC persisted in 39% of the 202 patients receiving prolonged antifungal treatment. Circulating interleukin-17A–producing T-cell count was low for most (82%) but not all of the patients tested. STAT1 GOF mutations underlie AD CMC, as well as an unexpectedly wide range of other clinical features, including not only a variety of infectious and autoimmune diseases, but also cerebral aneurysms and carcinomas that confer a poor prognosis.